Pressure cycle of superconducting Cs0.8Fe2Se2 : A transport study - Pedrazzini, Pablo (2011)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina